From leadership to performance: A structural model of knowledge management, team cohesion, and employee creativity in SOEs - Dewi, Ratih Komala; Hasmin, Hasmin (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
This study examines how leadership quality enhances knowledge management, team cohesion, employee creativity, and team performance. Using Structural Equation Modeling (SEM), results show that transformational leadership and organizational climate positively influence leadership quality, which fosters knowledge-sharing and teamwork. Knowledge management and team cohesion mediate the relationship between leadership and creativity, while psychological safety moderates the impact of cohesion on creativity. These findings highlight the importance of leadership in driving team effectiveness through indirect pathways. Organizations should invest in transformational leadership, psychological safety, and knowledge-sharing strategies to enhance innovation and performance. While the study contributes to leadership and organizational behavior literature, its cross-sectional design and industry-specific focus limit generalizability. Future research should explore longitudinal impacts and additional moderating factors across various sectors and cultures.